Assessment of Prevalence of Abnormal Neurological Findings on MRI in Patients Presenting with Chronic Headache: A Clinical Study - Shankarrao Patil, Pradeep; Bapu saheb Patil, Niranjan (Asian Journal of Medical Radiological Research, 2019)
Background: Chronic headache is one of the common presenting complaints in patients reporting to general practitioner. Magnetic resonance imaging (MRI) is a medical imaging technique used to aid diagnosis but unlike CT it does not use ionizing radiation. Hence; we assessed the prevalence of abnormal neurological findings on MRI in patients presenting with chronic headache. Subjects and Methods: A total of 100 patients reporting to the department with chief complaint of non-specific chronic headache were enrolled in the present study. Detailed demographic data and past medical history of all the patients was obtained. We also obtained complete history of present illness. MRI was done in all the patients under the hands of skilled and experienced radiologists. MRI findings were analyzed and were summarized in Microsoft excel sheet and were assessed by SPSS software. Chi- square test was used for assessment of level of significance. Results: Mean age of the patients of the present study was 40.8 years. Majority of the patients (49 percent) belonged to the age group of 30 to 50 years. 31 percent of the patients belonged to the age group of less than 30 years. 58 percent of the patients of the present study were males while the remaining 42 percent were females. Abnormal MRI findings were found to be present in 22 percent of the patient population. Conclusion: Chronic headache is a common problem affecting significant proportion of patient populating. Significant proportion of patients with chronic headache has associated abnormal MRI findings.